Desenvolvimento e caracterização de matrizes compósitas tridimensionais flexíveis de quitosana/vidro bioativo para aplicação potencial no tratamento e regeneração de lesões cutâneas - Talita Martins (2017)
Tissue engineering is a field of science that researches biological substitutes to support the restoration and improvement of the functions of tissues affected by injury or diseases. The skin lesions have great importance due the several functions of this tissue. Under normal circumstances, the wound healing progresses in an orderly manner. However, alterations called dermato proliferative disorders can occur. Due to these factors, there is a necessity for the development of topical coverage capable of allowing reepithelialization of the injured site in an orderly manner, aiding the healing process. An alternative is the production of flexible 3D composite matrices produced by foaming method, which support cell culture. These materials should have adequate porosity, appropriate pore size, interconnectivity, and mechanical behavior compatible with the features of native tissue. In this work, novel flexible 3D composite foams of chitosan (CH) combined with bioactive glass (BG) (SiO2-CaO-P2O5), in 1:0, 3:1 and 1:1 ratios, were developed using the sol-gel route and a foaming step, and characterized by several techniques. In addition to the effects of physical crosslinking expected by the incorporation of bioactive glass, it brings with it the improved antimicrobial character desired for the biomaterials intended for topical application. Physical characterization was performed by FTIR, XRD, Raman, SEM and micro-CT to evaluate the structural features, and also the porous structure of the samples. The mechanical features were evaluated by static compression and constant deflection compression tests. MTT, elution and LIVE/DEAD® assay was used to assess the cytotoxicity. Alkaline phosphatase activity was also measured. In vitro hydrolytic degradation of foams was evaluated by immersions in SBF for up to 84 days. Both scaffolds obtained presented a highly porous structure with interconnectivity. Our results revealed that CH/BG foams presented increased mechanical properties, increase of mass loss by degradation process, and a more homogeneous pore size and distribution, compared with the pure chitosan scaffold. The addition of the BG was able to modulate the permeation and water absorption capacity in the foams. The composites did not produce toxic effects. Therefore, the introduction of the inorganic phase into the chitosan matrix had a crucial effect on the morphologic and mechanical response of the flexible composite foams. These materials may be potential alternative scaffolds for use as wound dressings and scaffolds for tissue regeneration and healing stimulation.